2017
DOI: 10.1152/jn.00036.2017
|View full text |Cite
|
Sign up to set email alerts
|

Brain negativity as an indicator of predictive error processing: the contribution of visual action effect monitoring

Abstract: The error (related) negativity (Ne/ERN) is an event-related potential in the electroencephalogram (EEG) correlating with error processing. Its conditions of appearance before terminal external error information suggest that the Ne/ERN is indicative of predictive processes in the evaluation of errors. The aim of the present study was to specifically examine the Ne/ERN in a complex motor task and to particularly rule out other explaining sources of the Ne/ERN aside from error prediction processes. To this end, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 32 publications
(69 reference statements)
7
43
1
Order By: Relevance
“…Although a small negative deflection was also found in trials with positive feedback, the amplitude following negative feedback was significantly larger than after positive feedback. These findings are generally consistent with those reported in previous studies on outcome evaluation in cognitive tasks (Holroyd & Coles, ; Miltner et al, ; Nieuwenhuis et al, ) as well as in motor tasks (Joch et al, , ). Joch et al used a virtual throwing task and found similar effect sizes for the FRN (2017: d = 1.09; 2018: d = 1.21; current experiment: d = 1.34 [calculated from ηp2]).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although a small negative deflection was also found in trials with positive feedback, the amplitude following negative feedback was significantly larger than after positive feedback. These findings are generally consistent with those reported in previous studies on outcome evaluation in cognitive tasks (Holroyd & Coles, ; Miltner et al, ; Nieuwenhuis et al, ) as well as in motor tasks (Joch et al, , ). Joch et al used a virtual throwing task and found similar effect sizes for the FRN (2017: d = 1.09; 2018: d = 1.21; current experiment: d = 1.34 [calculated from ηp2]).…”
Section: Discussionsupporting
confidence: 92%
“…A negative deflection after positive feedback, as evident in the current experiment, is not always reported (Joch et al, ; Pfabigan et al, ). With respect to a similar error‐related EEG component, the error‐related negativity (ERN; Falkenstein, Hohnsbein, Hoormann, & Blanke, , Gehring, Goss, Coles, David, & Donchin, ), Coles, Scheffers, and Holroyd () argue that the ERN is sometimes observed on correct trials as well because error processing also occurs in these trials.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations